Thresholds of perception of mixed modulation - OZIMEK, Edward; SĘK, Aleksander (Archives of Acoustics, 1987)
This paper is concerned with the determination of perception thresholds of mixed modulation (MM) for chosen physical parameters of a signal. Besides a tonal modulating signal, also an irregular modulating signal in the form of a very narrow noise band with a definite mid-band frequency was applied in the course of research.It was stated that the perception of modulated signals is governed by two mechanisms: the time mechanism and the spectral mechanism, which do not depend on the type of modulation. These mechanisms become evident at definite values of the modulation frequency, which, as we know, conditions the rate of amplitude and frequency changes of the modulated signal.We have to do with the time mechanism at slow changes of physical parameters of this signal (low modulating frequency). Whereas, when the changes of these parameters are quick (high modulating frequency) the spectral mechanism takes place.The hypothesis concerning the existance of such perception mechanisms was confirmed by obtained experimental results.